Low Lymphocyte Count Is Associated With Radiotherapy Parameters and Affects the Outcomes of Esophageal Squamous Cell Carcinoma Patients - Wang, Xin; Zhao, Zongxing; Wang, Peiliang; Geng, Xiaotao; Zhu, Liqiong; Li, Minghuan (Frontiers in Oncology, 2020)
Purpose: Lymphocytes are central players in systemic anti-tumor immune responses. In this study, we aimed to identify the relationship between absolute lymphocyte count (ALC) nadir during definitive radiotherapy (RT) and survival outcomes in patients with esophageal squamous cell carcinoma (ESCC), as well as evaluate the effect of RT parameters on ALC during RT. Materials and methods: We retrospectively reviewed 189 patients with stage I-IVA ESCC, who were treated with definitive RT at a single institution between 2012 and 2015. ALC values were assessed before, weekly during RT, and one month after the end of RT. Kaplan–Meier and Cox regression analyses were used to evaluate the relationship between ALC nadir during RT and patient outcomes. Predictors of low ALC nadir were assessed using univariate and multivariate logistic regression analyses. Results: The median ALC before treatment was 1.73 × 109 cells/L. Fifty-eight (58.2) percent of the patients exhibited low ALC nadir (≤0.38 × 109 cells/L) during RT. A low ALC nadir during RT was significantly associated with poor OS, PFS, and LRFS. The planning target volume (PTV) was larger in patients with low ALC nadir compared with patients with high ALC nadir (418.5 cm3 vs. 347.7 cm3, P=0.023). Multivariate logistic regression analysis revealed that tumor stage III-IVA (P=0.002), low ALC before treatment (P=0.028), large Log10(PTV) (P=0.01), high heart V10 (P=0.003), and high heart V20 (P=0.028) were associated with low ALC nadir during RT. Conclusions: In ESCC patients who received definitive RT, a low ALC nadir during RT was associated with large PTVs, and it was an independent prognostic factor of outcomes.